Pengaruh Kualitas Produk dan Merek Terhadap Keputusan Pembelian Pada Madu Selandi - May Reni Br Sitepu; Syamsul Bahri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The purpose of this study was to determine whether product quality and brand reputation are relevant to the reasons for purchasing honey in Selandi District, Karo Regency. The data techniques used in this study include interviews, observations, and questionnaires. Cluster sampling, where the whole or part of the population is designated as the sample, is the sampling technique used. Data analysis used regressive multiple linear regression, hypothesis testing, coefficient of determination (R2), partial (t-test), simultaneous (f-test), and classical assumptions. In contrast to data collection using SPSS25, the findings of this study indicate that product and brand quality is able to clearly show the relationship between its findings and the majority (53%), which is in line with the estimated coefficient of determination of 0.535. Fcount 65.080 Ftable 2.45 with a significance of 0.000 from an alpha of 0.05 shows the results of the hypothesis. According to the study's findings, consumers' decisions to buy selandi honey are significantly and favorably influenced by the quality of brands and products.